(untitled) (International Journal of Physiotherapy, 2016)
Background: Cervical radiculopathy is a condition of pain and sensorimotor deficits due to cervical nerve root compression. The symptoms may include weakness, tingling, numbness and pain. C6, C7 nerve roots are most involved in cervical radiculopathy. Various modalities and therapeutic interventions are used and recommended for management of cervical radiculopathy including cervical collars, immobilization, manipulation, cervical traction TENS and therapeutic exercises.The aimof this study is to evaluate the efficacy of neurodynamics in comparison to manual traction in the management of cervical radiculopathy. Method: An Interventional research was performed in the Department of Physiotherapy, Mayo hospital Lahore, Pakistan. 40 subjects aged between 18-60 years participated in the study. They were divided into two groups namely Group A and Group B with 20 subjects in each group. The duration of the study was 4 weeks with 4 sessions per week. Group A received neurodynamics along with strengthening exercises while Group B received manual traction along with strengthening exercises. Neck Disability Index (NDI) scale was used as an outcome measure and paired sample t-test was used for statistical analysis. Results: A significant improvement was found in both neurodynamics group and manual traction group for pain and functional status with p value< 0.05. Conclusion: This study concluded that the treatment techniques, neurodynamics and manual traction were effective in alleviating the symptoms associated with cervical radiculopathy in terms of decreasing pain intensity, increasing ranges of motion and improving functional capacity.